Tolerable Constructive Graph-Based Hyper-Heuristic Algorithm For Examination Timetabling - Mohammad Pour, Shahrzad (2009)

(untitled)
Examination Timetabling Problem (ETTP) is an NP-hard typical optimization problem faced by institutions and universities across the world. This nature leads to heuristic methods cover a large branch of researches in this area. On the other hand, the problem varies from one institution to another, depending on the size, structure and constraints of that institution. Therefore generality of the proposed methods is one of the major goals in solving timetabling problem nowadays. These methods are trying to keep generality while adding to factors of these methods. Hyperheuristic is one of these approaches which make the basis of this thesis. In heuristic approaches getting stuck in local optimum is one of the propounded problems from early days. The main cause for the local optimal problem is that heuristic algorithms either focus on exploration (global improvement) rather than exploitation (local improvement) or vice versa.